The transformation of rural spatial form and its contributing factors in China: a literature review - Yue, Ma; Mohd Ariffin, Noor Fazamimah; Abdul Aziz, Faziawati; Xiao, He; Mengyao, Yu (Human Resources Management Academic Research Society (HRMARS), 2023)
Rural space is where rural folks live and rely on and is also a vital conduit for rural social and economic growth. Its distinct attractiveness from cities, is reflected in its unique and rich spatial shapes and dynamic layout. However, challenges have arisen in most of China's rural areas due to globalization and urban-rural convergence, necessitating the re-organization and re-planning of rural spaces. Since 1978, the Chinese government has aggressively pursued a series of new socialist rural policies, such as the construction of beautiful rural areas and the revitalization of the rural regions, to address many of the problems that have arisen due to industrialization and urbanization. This paper used the systematic review as an analysis method and explored the transformation of rural spatial form. The authors separated rural spaces into ecological, productive, and dwelling environments. According to the authors' assessment of the literature, the rural spatial form has undergone the following changes: (1) Rural production space has grown on the premise of occupying ecological and living areas, which is influenced by changes in the industrial structure; (2) The rise of rural tourism promotes the diversification of production and living space; (3) Rural tourism, modernization development, and rural living environment policies all have a direct impact on the surface form of living space. In a nutshell, the combined effects of society, economy, and politics have resulted in a change in the rural spatial layout.